KAJIAN AGAMA BUDDHA TENTANG PERLINDUNGAN PEREMPUAN - Andik Wijaya; Jeny Harianto; Mettadewi Wong (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
This research aims to provide solutions how to address various actions to women that happen happens. This research is aliterature study. This study uses a methodological approach, and the data obtained are concepts from various general literaturethat are relevant to the topic. The results of the research obtained are how to protect against acts of violence against womenthat occur due to human actions. By understanding and having love and compassion that manifests in the act of caring forwomen as a form of good morality, it will be able to provide maximum results in protecting women. By understanding eachother and the feeling of mutual need, the acts of violence against women will diminish.